A educação inclusiva nas escolas municipais de Uberlândia: dos anos 90 à primeira década do século XXI - Ranzatti, Raquel Magnólia Ferreira (2018)
In this research we bring the following problematic: how to set up the inclusive education in municipal schools of Uberlândia: the years of 1990 to the first decade of the 21st century? As our goal was to understand and reflect the special education in inclusive perspective from the formation of knowledge and practices of discourses that constituted to meet recapitulated liberal statesmanship, we seek to develop our work from eyes of observers and the discontinuities between historiography. For this, we brought our research approach the magnifying side observer who walks with Michel Foucault treating our object from the sinuosidades that had not yet been explored. Choose organize work into sections listed. In a first section, the introduction brought the memorial researcher collaboration to illustrate how the subject in research and also instigated the way that we set out to commit the same. In section II, "a look at the inclusive education in the light of Foucault's philosophy", we have writings of Michel Foucault and researchers that align to your thought for reflection on how to Work and the art of governing Liberal and Neoliberal if joining the norm, standardisation and proposal for inclusive education. In section III "The practices of inclusive education: from exclusion to inclusion" in descriptive form present as the discourses of knowledge produced socially for putting some practices of exclusion, segregation and integration collaborated for the years 90 1 construction of discourses of inclusive education. And, finally, in section IV, entitled "inclusive education in the municipality of Uberlândia deployment implementation" with some of the guidance documents of legislation worldwide, which guided public policy the federal and State level and the practice of Inclusive education in the municipality were able to realize how much the trajectory of the municipality contributed to the subjetivações that guided the control the bodies in the school space to happen and how the subject became subjetivados and lemmatized by knowledge and historical changes of discursive and non- discursive